Technology does not always teach distance learners, but effective distance teachers do… - Dzakiria, Hisham (Malaysian Educational Technology Association (META), 2004)
It has been said and accepted that teaching produces learning. This view is acclaimed in both the traditional, as well as in open distance learning (ODL). However, when we use technology for teaching distance courses, can we also assume that technology can produce effective distance learning? This may be true in some instances, and may not be true in other ODL circumstances;certainly generalising the first instances to be the case all the time will not be academically correct.This paper looks at distance learning as described by the learners - it is their story, their experience, and their perspective. In particular, this paper looks at the use of technology in distance learning at the Universiti Utara Malaysia (UUM), an issue that arose from discussions with the students, rather than being preordained by the research design. An important formidable task facing the UUM as an ODL provider is how to accommodate distance learners with different levels of preparedness. The gap between the most prepared and the least prepared learners in terms of using the technology in their learning are wide and growing. Persistent frustrations and learning setbacks were observed among the learners in this study. Evidently, technology does not always enhance students learning at a distance, but effective distance teachers who promote interaction, and provide sufficient learning support can make a different to distance learners. This article will also highlight the role of technology, learner support and the interactions in providing a better ODL learning outcomes.